Spatio-temporal dynamics of crop yields of corn in Poltava region - Пономаренко, С. В. (Scientific Progress & Innovations, 2017)
In the article we create methodical approaches to determine the impact of the yield of maize on regional factors, agro-economic, agro-technical and agro-economic nature. It was found that maize yields in the agricultural enterprises of Poltava region by region for 1995–2016 years on average varied in the range of 35.15±3.77 t/ha (Kobeliaky district) to 55.52±5.59 t/ha (Shyshaky district). The lowest level of variation of parameters yields of maize over the study period was typical for Orzhytsia district (28.64 % coefficient of variation), and the largest – for Chornuhy district (CV = 60,52 %). It is shown that the spatial variation of the component of the average level of maize yield statistically unreliable at present a large-scale level. The parameters of the linear model of the trend yield of corn are characterized by a spatial variation of its components. The analysis of the dynamics of the yield of corn in the agricultural enterprises of Poltava region in time indicates that there is a clear trend of increase in productivity during the study period, which can be described by linear regression. Regression coefficients are interpreted as over time the rate of growth of productivity and the potential yield in the initial period of the study.